The Influence of Netspeak on Students' Writing - Shalini Raj Thangaraj; Mahendran Maniam (Intelektual Pustaka Media Utama, 2015)
This study on Netspeak writes about words or phrases that are abbreviated and used frequently by Internet users. Language incorporates explosive items which need special care when handling the components in it. Wide knowledge regarding the various aspect of language will help readers to be able to handle the substance. Therefore, the author calls for a deeper comprehension of certain linguistic realities. This study helps to enlighten the various types of language used while using different mode of communication, thus avoiding harsh judgments regarding the informal use of language. The study also hopes to show that there is nothing linguistically eccentric about using Netspeak while communicating online. They are regarded a negative influence only if they are used in a formal environment. This study deals with the notion that Netspeak is a common language used especially by the younger generation to communicate with one another while online. Although, most educators have regarded the influence of Netspeak as negative and detrimental towards students’ writing, however, Netspeak is still prevalent. This study also gives the statement of problem, its objectives, significance and limitations. It is hoped that the people in the society, especially educators will not view Netspeak as only a cause of the decline of students’ writing standard, but a fixture in language, which is acknowledged for its passing style and momentary trend.